2006
DOI: 10.1542/peds.2005-0620c
|View full text |Cite
|
Sign up to set email alerts
|

Summary Proceedings From the Neonatal Pain-Control Group

Abstract: Recent advances in neurobiology and clinical medicine have established that the fetus and newborn may experience acute, established, and chronic pain. They respond to such noxious stimuli by a series of complex biochemical, physiologic, and behavioral alterations. Studies have concluded that controlling pain experience is beneficial with respect to short-term and perhaps long-term outcomes. Yet, pain-control measures are adopted infrequently because of unresolved scientific issues and lack of appreciation for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
137
0
23

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(162 citation statements)
references
References 161 publications
(192 reference statements)
0
137
0
23
Order By: Relevance
“…However, neonatal pain assessment is not an easy task and the existence of several scales can be confusing. 53 More research is needed on the implementation of pain scales at the bedside and on the ways of optimising pain management with pain assessments in neonates. Opioids or benzodiazepines were weaned gradually in 39%, 31%, and 42% of neonates in the TV, NIV, and SV groups, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…However, neonatal pain assessment is not an easy task and the existence of several scales can be confusing. 53 More research is needed on the implementation of pain scales at the bedside and on the ways of optimising pain management with pain assessments in neonates. Opioids or benzodiazepines were weaned gradually in 39%, 31%, and 42% of neonates in the TV, NIV, and SV groups, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, there is an urgent need for high-quality studies in neonates and infants. Nevertheless, despite a few initiatives to promote research in neonates, [32] most paediatric studies are done in children and adolescents, as shown by a study of 253 trials conducted to obtain paediatric exclusivity extensions. [33] Drugs studied in these trials are mainly used in older children and adolescents for conditions such as hypertension, systemic autoimmune disorders, and gastrointestinal disorders.…”
Section: /25mentioning
confidence: 99%
“…In a similar way, pain in human newborns was ignored for a long time. Their capacity to feel pain and, more generally, to undergo a stress when submitted to surgical operations or diverse manipulations has been studied only relatively recently (see, for instance, Anand, 1990;Gunnar et al, 1988 and1992;Anand et al, 2006). Post-operative pain and chronic health problems Pain associated with amputation and other surgical interventions is not limited to the time of the operation.…”
Section: Cosmetic Aspectsmentioning
confidence: 99%